2013
DOI: 10.1666/0094-8373-39.1.21
|View full text |Cite
|
Sign up to set email alerts
|

The cryptic and the apparent reversed: lack of genetic differentiation within the morphologically diverse plexus of the planktonic foraminifer Globigerinoides sacculifer

Abstract: International audiencePrevious genetic studies of extant planktonic foraminifera have provided evidence that the traditional, strictly morphological definition of species in these organisms underestimates their biodiversity. Here, we report the first case where this pattern is reversed. The modern (sub)tropical species plexus Globigerinoides sacculifer is characterized by large morphological variability, which has led to the proliferation of taxonomic names attributed to morphological end-members within the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 64 publications
8
74
2
Order By: Relevance
“…Our results are in stark contrast to the numerous recent studies on protists showing cases of cryptic genetic diversity, where genetic divergence is not reflected in morphological differentiation (for example, Coleman, 2001). We have only found one other similar study in which four marine foraminifera morphospecies were shown to be virtually identical by SSU rDNA and ITS-1 DNA markers (André et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are in stark contrast to the numerous recent studies on protists showing cases of cryptic genetic diversity, where genetic divergence is not reflected in morphological differentiation (for example, Coleman, 2001). We have only found one other similar study in which four marine foraminifera morphospecies were shown to be virtually identical by SSU rDNA and ITS-1 DNA markers (André et al, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Each morphospecies is distinguishable by its chamber arrangement, growth ratio of chambers, and shape of the last chamber. Surprisingly, however, G. sacculifer has only one genotype, and there is no relationship between the morphologic divergence and genetics (André et al 2013). From the viewpoint of molecular phylogeny, this suggests a delimitation of classification based on tradi-tional morphology.…”
Section: Reassessment Of Shell Morphologymentioning
confidence: 97%
“…Globigerinoides sacculifer, a tropical species, has various morphologic types in the world ocean. André et al (2013) carried out a world survey of two ribosomal DNA regions (SSU and ITS-1) in different morphotypes of G. sacculifer, including G. trilobus, G. immaturus, G. quadrilobatus, and typical G. sacculifer itself.…”
Section: Reassessment Of Shell Morphologymentioning
confidence: 99%
“…Preservation in ethanol, a hypothetical third option commonly used for metazoans, is not recommended for foraminifera as it inhibits the amplification of DNA by PCR (Holzmann and Pawlowski, 1996;Lecroq, 2014). Drying and freezing has been used preferably in the last years, since it allows faster handling of foraminiferal specimens (André et al, 2013;Weiner et al, 2014Weiner et al, , 2015. A considerably larger number of specimens can be preserved using this method, as it does not involve individual selection and placement in microtubes immediately after sampling.…”
Section: Preservation Of Specimensmentioning
confidence: 99%
“…Using the small subunit ribosomal RNA gene (SSU rDNA) as a marker, hidden genetic diversity was discovered within established morphospecies (Huber et al, 1997;de Vargas et al, 1999). This triggered a series of subsequent studies that screened morphospecies for their cryptic diversity (e.g., Darling et al, 1999;de Vargas et al, 1999;Aurahs et al, 2009a;Morard et al, 2009Morard et al, , 2011Weiner et al, 2012Weiner et al, , 2014André et al, 2013).…”
Section: Introductionmentioning
confidence: 99%